Comprehensive metabolic analyses provide new insights into primary and secondary metabolites in different tissues of Jianghua Kucha tea (Camellia sinensis var. assamica cv. Jianghua) - Wu, Wenliang; Shi, Jiang; Jin, Jiqiang; Liu, Zhen; Yuan, Yong; Chen, Zhida; Zhang, Shuguang; Dai, Weidong; Lin, Zhi (Frontiers in Nutrition, 2023)
Jianghua Kucha (JHKC) is a special tea germplasm with enriched specialized metabolites, including theacrine, non-epi-form flavanols and methylated-flavanols. However, the accumulation patterns of metabolites in different tissues of JHKC are unclear. In this study, the changes of primary and secondary metabolites as well as related metabolic pathways were investigated by metabolomics analysis. Significant differences were observed in 68 primary and 51 secondary metabolites mainly related with the pathways of starch and sucrose, amino acids, caffeine, and flavanols metabolism and TCA cycle. The bud exhibited higher levels of glucose-6-phosphate, citric acid, most amino acids, theobromine, catechin-gallate, epicatechin-gallate, procyanidins, and theasinensins; the 1st leaf showed higher levels of caffeine and epigallocatechin-3-gallate; and the 4th leaf contained higher levels of most monosaccharides, theacrine, and epigallocatechin-3-O-(3″-O-methyl)-gallate. In addition, primary metabolites and important secondary metabolites had certain correlations. This study provides comprehensive insight into primary and secondary metabolites in JHKC and offers guidelines for efficiently utilizing specialized metabolites of JHKC in the future.